2020
DOI: 10.1182/blood-2020-134835
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Doses of Anticoagulation Are Associated with Improved Survival in Hospitalized COVID-19 Patients

Abstract: Background: Hypercoagulability may contribute to COVID-19 pathogenicity. Evidence comparing clinical outcomes among patients with COVID-19 receiving therapeutic compared to prophylactic dose anticoagulation is limited. We evaluated whether therapeutic anticoagulation (tAC) is associated with improved survival compared to prophylactic (pAC) and no anticoagulation (AC) in hospitalized COVID-19 patients. Methods: This was a retrospective, multi-center cohort study of consecutive COVID-19 patients a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…[43][44][45] Retrospective studies of therapeutic-compared to prophylactic-dose anticoagulation have reported mixed effects on mortality, while only two small studies have examined outcomes with intermediate-compared to prophylactic-dose anticoagulation, largely focusing on venous thromboembolism rates, again with conflicting results. 7,15,16,[18][19][20][21][22]46,47 More recently, the ACTIV-4a randomized clinical trial showed efficacy of therapeutic-compared to prophylactic-dose anticoagulation in noncritically ill COVID-19 patients but futility among critically ill patients. 23,24 Our analysis is the first large-scale study to specifically examine intermediate-and prophylactic-dose anticoagulation in COVID-19.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[43][44][45] Retrospective studies of therapeutic-compared to prophylactic-dose anticoagulation have reported mixed effects on mortality, while only two small studies have examined outcomes with intermediate-compared to prophylactic-dose anticoagulation, largely focusing on venous thromboembolism rates, again with conflicting results. 7,15,16,[18][19][20][21][22]46,47 More recently, the ACTIV-4a randomized clinical trial showed efficacy of therapeutic-compared to prophylactic-dose anticoagulation in noncritically ill COVID-19 patients but futility among critically ill patients. 23,24 Our analysis is the first large-scale study to specifically examine intermediate-and prophylactic-dose anticoagulation in COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 Some retrospective studies have observed lower mortality rates with therapeutic-dose anticoagulation compared to either prophylacticdose anticoagulation or no anticoagulation, while others comparing therapeutic-and prophylactic-dose anticoagulation have found no mortality difference. [15][16][17][18][19][20][21][22] Recent findings from the ACTIV-4a randomized controlled trial showed that therapeutic-compared to prophylactic-dose anticoagulation improved outcomes among non-critically ill patients but not among critically ill COVID-19 patients. 23,24 To date, however, no large-scale study has compared the effects of intermediate-versus prophylactic-dose anticoagulation.…”
Section: Introductionmentioning
confidence: 99%